Venture Investment in The Small Entrepreneur Companies (International Journal of Applied Research in Management and Economics, 2018)
Since one of the major problems for entrepreneurs to create and register small companies and their inventions is the lack of support of managers to drive them into venture investments, which is one of the ways of financing companies. Therefore, in this research, we have tried to find ways to solve and Review these problems. In this study, the stages of growth and development, innovation characteristics, specific problems of financing small enterprises, venture investments, risk capital outflows, types of investments, venture investment process and the main indicators of venture investments have been discussed. The result of this study showed that the government, the levers of financial encouragement, taxes, intellectual property, labor law, experienced and trained managers, the rules governing the activities of banks, insurance companies and retirement funds, the motivation for wealth creation and networking have a significant role in Encouraging small entrepreneurs to invest in risk.